Study on the Anti-snake venom property of Cabbage (International Journal of Innovative Research in Computer Science & Technology, 2022)
Snake poison causes death and tissue  disfiguration among the rural people. Though anti-dote or  anti-snake venom serum is freely accessible at government  health care facilities but is hampered by poor handling,  storage and lack of specificity. The necessity of the hour is  to find new anti-dotes which are not only inexpensive but  can work against a broad variety of snake venoms. In India,  most of the poisonous snakes belong to the Elapidae &  Viperidae families. In this study, venom of the Flavonoids  has been found to have anti-snake venom action owing to  which the cabbage was chosen for its high flavonoid  content. For this, initially the effective concentration of the  Russell’s viper was found on goat’s plasma at 4.54 g/mL  and the aqueous extract of cabbage was observed to inhibit  proteolysis. Next, the minimal coagulant dosage (MCD)  was estimated as 3.69 µg/ml for goat’s plasma and the  aqueous extract of cabbage was found to delay venom  induced plasma clotting. An examination of these findings  suggest that cabbage may be utilized a source of anti-snake  venom.
Keywords: Antidote; Anti-Snake Venom; Clotting; Concentration; Minimum Coagulant Dosage